IMPLEMENTATION OF QRIS-BASED PAYMENT GATEWAY IN MOBILE BANKING AND ITS IMPACT ON TRANSACTION SMOOTHNESS OF MSMES IN COASTAL TOURISM AREAS OF KUPANG CITY - Hapsa Usman; Nonce F. Tuati; Deetje W. Manuain (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the implementation of a QRIS-based payment gateway through mobile banking applications and its impact on transaction smoothness among micro, small, and medium enterprises (MSMEs) operating in coastal tourism areas of Kupang City. The increasing adoption of cashless payment systems has encouraged MSMEs to integrate digital transactions into daily business activities, particularly in tourism-based economic settings characterized by high transaction intensity. This research employs a qualitative descriptive–interpretative approach, with data collected through semi-structured interviews, direct observations, and documentation involving 100 MSME actors located in Lasiana Beach, Oesapa Beach, Kelapa Lima Beach, and Tedys Beach.Data analysis was conducted using NVivo software following the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing. The findings indicate that QRIS implementation improves transaction speed, efficiency, and convenience, while reducing dependence on cash transactions. MSME actors also perceive QRIS as a secure payment system due to its integration with formal banking institutions. However, challenges such as limited digital literacy, unstable internet connectivity, and insufficient technical assistance hinder optimal utilization. This study highlights the importance of combining digital payment adoption with continuous education and infrastructure support to ensure sustainable digital transformation of MSMEs.